(3aJM GdeHOY aj TQM GdebfYs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3eMeO GdWfOfGdi GdCRgQi s)
(3ChdgG (B:s
,(3HYO aEf GdebfY GdefXhe Ydi HMQ GdWhjd ai Yde GdLHQ hGdebGHdI ddEeGe GHf GdgGFe WdH efi HYV GdCYRg Ydi Gf GVY Ydjg TQMkG jMd CdaGXg s
(3BNQgG (B:s
(3Ydi gPgg GdbUjOI eJcGedI HeG GTJedJ Ydjg ef GdahGFO hGddg GdgGOi ddUhGH hEdjg GdeQLY hGdeBH s
(3GdebfY GfXQ cTa GdXfhf M(B2 (3U` (B1089s
(3GdfSNI HgG MhGTs
(3HBNQg aGFOgZes
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdQjGVjGJs